Research on developing diesel jets in combustion chamber dual Fuel Biogas – Diesel engine with different CH4 ingredients - Nguyễn Việt Hải; Bùi Văn Ga (Journal of Technical Education Science, 2017)
Simulation of vaporization of diesel jets in air-biogas mixture is carried out with CFD software FLUENT. The results show that at the same temperature, injection of diesel jets in air approaches its vaporization in CO2 at low pressure but approaches its vaporization in CH4 in high pressure. In biogas-air mixture, vaporization of diesel jet depends on CH4/CO2 ratio in the fuel. In the same injection conditions and mixture components, vaporization of diesel jets decreases as pressure increases but it increases sharply when the temperature of the mixture in the combustion chamber goes up. With the same diesel quantity injected into combustion chamber, vaporization increases as jet flow goes up.